Pengaruh CAR, LDR, BOPO dan NPL terhadap ROA pada Sektor Perbankan di Bursa Efek Indonesia Periode 2018-2019 - Ahmad Rafinur; Artie Arditha; Rusmianto Rusmianto (Jurnal Ilmiah ESAI, 2023)
This study aims to determine the effect of CAR, LDR, BOPO and NPL on ROA in the banking sector in the Indonesian stock exchange. Using Purposive Sampling method, involving 2018-2019 periods, the current research obtained 33 companies that meet the criteria, so the total number of samples is 66 company financial reports. The method of data collection is through secondary data documentation obtained from downloading financial reports published by www.idx.co.id. The results of this study indicate that CAR and NPL have no effect on ROA, while LDR, BOPO have effects on ROA. And  CAR, LDR, BOPO and NPL collectively affect ROA